Diaprepes in Florida citrus: Past, present, and future. - Stelinski, Lukasz; Diepenbrock, Lauren; Duncan, Larry (EDIS, 2023)
In response to the recent resurgence of Diaprepes under a scenario where most citrus trees are infected with HLB, we have begun work to develop the needed tools and management recommendations to limit the damage it might cause. The use of landscape fabric was shown to increase citrus tree growth rate and is thought to greatly reduce the population density of Diaprepes; however, experimental validation is lacking. We are hoping to establish a trial in which landscape fabric is installed in the tree rows mechanically. The effects of landscape fabric need to be investigated by determining effects on tree infestation by Diaprepes, health and yield in future years as compared with no fabric controls in replicated field trials. For example, even if fabric reduces weevil damage, it is unknown whether trees debilitated by HLB can respond sufficiently to make fabric installation profitable. Therefore, we also need to evaluate fabric performance when 1) combined with EPN to control larvae in the root system crown and 2) combined with individual tree covers (IPC) for control of HLB. In the coming years, we also plan to determine which currently available and new insecticides are useful against Diaprepes and the required rates to update management recommendations. Finally, we still need to determine the common source of Diaprepes infestations and accurately quantify the movement patterns of beetles between non-host-habitats outside of groves, grove borders, and grove interiors. Determining the source of Diaprepes infestation and where Diaprepes invade groves may allow us to target the source of these invasions to stop prevent or limit infestations prior to the need for whole-grove sprays.